New curing agents for epoxy resins: protoporphyrins. (8th August 2017) - Fraga‐López, Francisco; Vázquez Barreiro, Eva C.; Jover, Aida; Meijide, Francisco; Rodríguez, Eugenio; Vázquez‐Tato, José
Abstract : Two similar macrocycles protoporphyrin IX and zinc protoporphyrin IX (ZPP) have been used as cross‐linking agents for curing the epoxy resin of bisphenol A diglycidyl ether (BADGE, n = 0). The enthalpies and the activation energies of the esterification reaction of the 2 systems are very close to each other. However, the temperature of the minimum in the differential scanning calorimetry thermogram is 38°C lower for BADGE (n = 0)/ZPP, thus requiring a less energy expenditure for curing the system. By the contrary, the enthalpy and activation energies for the etherification reaction are lower and higher, respectively, for BADGE (n = 0)/ZPP suggesting that the zinc ion affects it, although the involved mechanism is unknown.